2007
DOI: 10.1073/pnas.0606914104
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of protein complexes within and across species

Abstract: Yeast two-hybrid and coimmunoprecipitation experiments have defined large-scale protein-protein interaction networks for many model species. Separately, systematic chromatin immunoprecipitation experiments have enabled the assembly of large networks of transcriptional regulatory interactions. To investigate the functional interplay between these two interaction types, we combined both within a probabilistic framework that models the cell as a network of transcription factors regulating protein complexes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…For instance, among the functional categories enriched in transcriptional FFL clusters, we find mainly the core processes associated with transcription such as transcriptional control, DNA binding and regulation of metabolic processes (Supplementary Table S1), supporting the hypothesis that transcriptional FFLs play a universal information-processing role 24 . For the transcriptionally coregulated interacting proteins motif, it is usually assumed that enrichment and clustering reflects a 'regulonic complex' theme in which transcriptionally coregulated interacting proteins are often members of a protein complex 3,4,25 . We found that high-scoring coregulated protein clusters sometimes overlap with known protein complexes (Supplementary Table S2), but more often form 'functional protein networks' 26 ( Figure 2A(2)): subnetworks of the PPI network enriched for a particular function and identified by overlaying the protein interaction network with an additional layer of information, in this case regulator-target data.…”
Section: Comparison With Zhang Et Almentioning
confidence: 99%
“…For instance, among the functional categories enriched in transcriptional FFL clusters, we find mainly the core processes associated with transcription such as transcriptional control, DNA binding and regulation of metabolic processes (Supplementary Table S1), supporting the hypothesis that transcriptional FFLs play a universal information-processing role 24 . For the transcriptionally coregulated interacting proteins motif, it is usually assumed that enrichment and clustering reflects a 'regulonic complex' theme in which transcriptionally coregulated interacting proteins are often members of a protein complex 3,4,25 . We found that high-scoring coregulated protein clusters sometimes overlap with known protein complexes (Supplementary Table S2), but more often form 'functional protein networks' 26 ( Figure 2A(2)): subnetworks of the PPI network enriched for a particular function and identified by overlaying the protein interaction network with an additional layer of information, in this case regulator-target data.…”
Section: Comparison With Zhang Et Almentioning
confidence: 99%
“…Secondly, there are several types of possible interactions in living cells, from stable complexes up to temporary, functional pairings (for example, during the phosphorylation process in response to external stimuli). Protein complexes are better preserved during the evolution process than single proteins, so some computational methods focus on the prediction or searching of complexes that are common to several species [5][6][7][8][9][10][11][12]. Those methods use available information about experimentally verified interactions between proteins, orthologies, and comparison of protein sequences [13].…”
Section: Introductionmentioning
confidence: 99%
“…As more experimental data gathers and network integration algorithms improve, network datasets with multiple data types will appear (Srinivasan et al, 2007), such as networks with interactions between proteins and DNA (Zhang et al, 2005;Tan et al, 2007), networks with physical as well as genetic interactions (Kelley and Ideker, 2005;Ulitsky et al, 2008), expression networks with boolean edges (Sahoo et al, 2007), and metabolic networks with chemical compounds (Kuhn et al, 2007). With future work to redefine Graemlin 2.0's feature functions, its scoring function and parameter learning algorithm will apply to these kinds of networks.…”
Section: Discussionmentioning
confidence: 99%